Analisis Kesalahan Esensial Hasil Pengelasan Peserta Lomba Kompetensi Siswa SMK Tingkat Daerah Istimewa Yogyakarta - Putut Hargiyarto; Arif Marwanto; Riswan Dwi Djatmiko (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
The purpose of this study is to examine various defects in the welding joint works from the participants of Vocational High School students’ skills competition in Yogyakarta area for welding field. This study can be categorized as a qualitative descriptive study. The data collection method was using documentation. The data was analyzed using descriptive qualitative technique. The results showed that in the preparation, the students were lack of understanding and knowledge in determining the welding requirements, the welding current, the type of electrodes SMAW. In the welding process, some participants did not fulfil the welding procedure during the welding process such as mistakes in setting up the SMAW machine, setting the welding current properly, selecting an electrode based on the type and thickness of the workpiece, and mistakes in the process of fit up. In the post-welding process, there were a few mistakes such as the grinding process to clean weld spatter that damaged the ridge.